MXene-coated BN heterostructure heat-conducting filler, epoxy composite material thereof and preparation methods of MXene-coated BN heterostructure heat-conducting filler and epoxy composite material
The preparation of MXene@BN heterostructure thermal conductivity filler by electrostatic self-assembly method solves the problem of insufficient inherent thermal conductivity of epoxy resin composites, and achieves a combination of high thermal conductivity and good electrical insulation performance under less filler load.
Patent Information
- Application Number
- CN202411867158.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The inherent thermal conductivity of existing epoxy resin composite materials is insufficient and cannot meet the efficient heat dissipation needs of electronic devices. At the same time, increasing the amount of thermally conductive filler will lead to filler agglomeration, deterioration of material processing performance, and degradation of mechanical properties.
The MXene@BN heterostructure thermal conductivity filler was prepared by electrostatic self-assembly method. By modifying boron nitride and MXene nanosheets, modified boron nitride with positive charge on the surface and modified MXene with negative charge on the surface were formed. The electrostatic action was used to self-assemble to obtain fillers with high thermal conductivity and excellent electrical insulation.
The thermal conductivity of epoxy composite materials is significantly improved under less filler load, while maintaining good electrical insulation performance, solving the problem of material performance degradation caused by high traditional filler usage.
Smart Images

Figure BDA0005194716070000021 
Figure BDA0005194716070000022 
Figure BDA0005194716070000051
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of epoxy resin composite materials, and relates to a preparation method of a MXene@BN heterostructure thermal conductive filler using the synergistic effect of two fillers and an epoxy composite material thereof. Background Art
[0002] With the rapid development of electronic technology, the integration of electronic devices is constantly improving, and the power density is also increasing. If the large amount of heat generated during the working process cannot be effectively dissipated, it will affect the performance of the device. Epoxy resin is widely used as an electronic packaging material due to its good mechanical properties, electrical insulation and chemical corrosion resistance. Electrical insulation and thermal conductivity are important indicators of electronic packaging materials. The volume resistivity of epoxy resin is greater than 10 15 Ω·m, meeting the requirements of electronic packaging (greater than 10 12 Ω·m). However, the inherent thermal conductivity is usually only 0.18~0.22W / m·K, which cannot meet the efficient heat dissipation requirements of electronic devices. Adding thermally conductive fillers is the most common method to improve the thermal conductivity of epoxy resin. However, in order to obtain high thermal conductivity, a high amount of filler is often required, which inevitably leads to problems such as filler agglomeration, poor material processing performance, and decreased mechanical properties.
[0003] Due to their unique structural and morphological characteristics, heterogeneous structure fillers are more likely to form heat conduction pathways, thereby achieving a higher thermal conductivity improvement effect than single or simply blended fillers.
[0004] Chinese invention patent CN202110371409.4 discloses a method for preparing an Al2O3@BN / epoxy composite material. When the amount of thermal conductive filler is 30wt%, the thermal conductivity of the composite material reaches 0.84W / m·K. Chinese invention patent CN202211629533.7 discloses a method for preparing a MXene@silver / polyvinyl alcohol composite material. When the amount of thermal conductive filler MXene@silver is 60wt%, the thermal conductivity of the composite material reaches 3.72W / m·K. However, the electrical conductivity is as high as 156S / m, which cannot meet the requirements of electrical insulation of electronic packaging materials. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a MXene@BN heterostructure thermal conductive filler and an epoxy composite material thereof, which can obtain an epoxy composite material with high thermal conductivity and excellent electrical insulation under less filler loading. To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A method for preparing a MXene@BN heterostructure thermal conductive filler, characterized in that the method comprises the following steps:
[0007] 1) using a cationic modifier to modify the boron nitride nanosheets, adding the boron nitride nanosheets to an aqueous solution of the cationic modifier at a mass ratio of (1-10):1, at a modification temperature of 15-50° C., and for a modification time of 6-36 hours, to obtain modified boron nitride nanosheets with a positive charge on the surface;
[0008] 2) Modifying the MXene nanosheets with an anionic modifier, adding the MXene nanosheets to an aqueous solution of the anionic modifier at a mass ratio of MXene nanosheets to anionic modifier of (1-10):1, at a modification temperature of 15-50°C, and for a modification time of 6-36h, to obtain modified MXene nanosheets with negatively charged surfaces;
[0009] 3) electrostatically self-assemble the modified boron nitride nanosheets and the modified MXene nanosheets in a mass ratio of (10-100):1, at a temperature of 10-50° C., to obtain a MXene@BN heterostructure thermal conductive filler;
[0010] Wherein, the MXene nanosheet is prepared as follows:
[0011] Prepare a solution with concentrated hydrochloric acid and distilled water in a volume ratio of (2-4):1, stir and mix evenly, then add lithium fluoride, wherein the mass ratio of lithium fluoride to concentrated hydrochloric acid is 1:(10-20), slowly add Ti3AlC2 to the above solution, and stir at a temperature of 30-50°C for 1-2 days, wherein the mass ratio of Ti3AlC2 to lithium fluoride is 1:(1-2); after the reaction is completed, pour into a centrifuge tube and shake evenly, centrifuge for 5-8 minutes, pour out the supernatant, add 1M hydrochloric acid to the centrifuge tube, repeat the above centrifugation step 3-5 times, then pour out the supernatant, add appropriate amount of distilled water to the centrifuge tube, repeat the above centrifugation step 5-7 times, then pour out the upper layer, collect the bottom precipitate, add appropriate amount of distilled water, and ultrasonicate at room temperature for 40-70 minutes under nitrogen atmosphere, centrifuge the above mixed solution for 10-15 minutes, take the upper layer, and freeze-dry to obtain MXene nanosheets.
[0012] The cationic modifier is at least one selected from hexadecyltrimethylammonium chloride, polydimethyldiallylammonium chloride, and polydimethylsiloxane; the anionic modifier is at least one selected from polyvinyl alcohol sulfonate, sodium lauryl sulfate, and sodium polyacrylate.
[0013] The present invention also provides an epoxy composite material of MXene@BN heterostructure thermal conductive filler prepared by the above method, characterized in that the components and mass fractions of the epoxy composite material are as follows:
[0014]
[0015] The epoxy resin is one selected from bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic polyepoxy resin, alicyclic epoxy resin, and aliphatic epoxy resin; the curing agent is an amine curing agent or an acid anhydride curing agent; and the accelerator is one selected from phenol accelerators, tertiary amine accelerators, and substituted urea accelerators.
[0016] Preferably, the bisphenol A epoxy resin is epoxy resin E-51 or epoxy resin E-44, the bisphenol F epoxy resin is epoxy resin EP-862; the anhydride curing agent is selected from methyl hexahydrophthalic anhydride or maleic anhydride, the amine curing agent is 4,4'-diaminodiphenylmethane or 4,4'-diaminodiphenyl sulfone; the tertiary amine accelerator is 2,4,6-tris(dimethylaminomethyl)phenol or benzyldimethylamine.
[0017] Preferably, the components and mass fractions of the epoxy composite material are as follows:
[0018]
[0019] The present invention further provides a method for preparing the above-mentioned epoxy composite material, characterized in that the epoxy resin, curing agent and accelerator are evenly mixed according to the above-mentioned proportions, and then the MXene@BN heterostructure thermal conductive filler is added, and the thermal conductive filler is evenly dispersed by stirring or ultrasonic vibration. After curing, the epoxy composite material is naturally cooled to obtain the above-mentioned epoxy composite material.
[0020] The present invention is beneficial in that:
[0021] On the one hand, the thermally conductive filler with a heterogeneous structure is obtained through electrostatic self-assembly, and the preparation method is simple, efficient, and low-cost, which is conducive to large-scale industrial production.
[0022] On the other hand, compared with zero-dimensional fillers, two-dimensional sheet-structured fillers have a larger diameter-to-thickness ratio and are more likely to contact each other in the matrix to form an effective thermal conductivity network. The introduction of MXene with higher thermal conductivity into the boron nitride layer through electrostatic action can significantly increase the thermal conductivity of the composite filler. At the same time, because MXene is sandwiched between the insulating boron nitride layers, the conductivity of the composite filler does not increase significantly, and can simultaneously meet the electrical insulation requirements of electronic packaging materials. DETAILED DESCRIPTION
[0023] The present invention will be further described below by way of examples.
[0024] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0025] Embodiment 1:
[0026] 10 g of modified boron nitride nanosheets were added to an aqueous solution of 1 g of polydienyldimethylammonium chloride, and the mixture was stirred at room temperature for 12 hours to obtain modified boron nitride nanosheets.
[0027] 10 g of MXene nanosheets were added to 1 g of sodium polyacrylate aqueous solution and stirred at room temperature for 12 hours to obtain modified MXene nanosheets.
[0028] The above-mentioned 10 g of modified boron nitride and 0.1 g of modified MXene were added to deionized water and stirred at room temperature for 2 hours to obtain a MXene@BN heterostructure thermal conductive filler.
[0029] The above 3.45 g MXene@BN was added into a mixture of 8 g E51 epoxy resin, 5.84 g methylhexahydrophthalic anhydride curing agent and 0.12 g 2,4,6-tris(dimethylaminomethyl)phenol, mixed evenly, cast into a mold after degassing, and naturally cooled after curing to obtain an epoxy composite material.
[0030] Example 2
[0031] 10 g of boron nitride nanosheets with hydroxyl groups were added to 1 g of an aqueous solution of hexadecyltrimethylammonium chloride, mixed evenly, and stirred at room temperature for 16 hours to obtain modified boron nitride nanosheets.
[0032] 10 g of MXene nanosheets were added to 1 g of sodium polyacrylate aqueous solution, mixed evenly, and stirred at room temperature for 16 hours to obtain modified MXene nanosheets.
[0033] 10 g of modified boron nitride and 0.2 g of modified MXene were added to deionized water and stirred at room temperature for 4 hours to obtain MXene@BN heterostructure thermal conductive filler.
[0034] The above 3.45 g MXene@BN was added into a mixture of 6.95 g EP 862 epoxy resin, 6.95 g methylhexahydrophthalic anhydride curing agent and 0.06 g 2,4,6-tris(dimethylaminomethyl)phenol, mixed evenly, cast into a mold after degassing, and naturally cooled after curing to obtain an epoxy composite material.
[0035] Example 3
[0036] 10 g of boron nitride nanosheets with hydroxyl groups were added to 1 g of an aqueous solution of polydienyldimethylammonium chloride, mixed evenly, and stirred at room temperature for 24 hours to obtain modified boron nitride nanosheets.
[0037] 10 g of MXene nanosheets were added to 1 g of the aqueous solution of polyvinyl alcohol sulfonate, mixed evenly, and stirred at room temperature for 24 hours to obtain modified MXene nanosheets.
[0038] 10 g of modified boron nitride and 0.5 g of modified MXene were added to deionized water and stirred at room temperature for 6 hours to obtain MXene@BN heterostructure thermal conductive filler.
[0039] The above 4.64 g MXene@BN was added into a mixture of 10.47 g E51 epoxy resin and 3.49 g 4,4'-diaminodiphenyl sulfone, mixed evenly, degassed and molded, and then naturally cooled after curing to obtain an epoxy composite material.
[0040] Example 4
[0041] 10 g of boron nitride nanosheets with hydroxyl groups were added to 1 g of the aqueous solution of polydimethylsiloxane, mixed evenly, and stirred at room temperature for 30 hours to obtain modified boron nitride nanosheets.
[0042] Add 10 g of MXene nanosheets to 1 g of an aqueous solution of sodium dodecyl sulfate, mix well, and stir at room temperature for 30 hours to obtain modified MXene nanosheets.
[0043] 10 g of modified boron nitride and 0.5 g of modified MXene were added to deionized water and stirred at room temperature for 8 hours to obtain MXene@BN heterostructure thermal conductive filler.
[0044] The above 4.64 g MXene@BN was added into a mixture of 8 g E51 epoxy resin, 5.84 g methylhexahydrophthalic anhydride curing agent and 0.12 g 2,4,6-tris(dimethylaminomethyl)phenol, mixed evenly, cast into a mold after degassing, and naturally cooled after curing to obtain an epoxy composite material.
[0045] Comparative Example 1
[0046] 9g of E51 epoxy resin and 3g of 4,4'-diaminodiphenyl sulfone were mixed evenly, degassed and molded, and then naturally cooled after curing to obtain an epoxy composite material.
[0047] Comparative Example 2
[0048] 4.64 g of boron nitride nanosheets were added into a mixture of 6.95 g of EP 862 epoxy resin, 6.95 g of methylhexahydrophthalic anhydride curing agent and 0.06 g of 2,4,6-tris(dimethylaminomethyl)phenol, mixed evenly, molded after degassing, and naturally cooled after curing to obtain an epoxy composite material.
[0049] Comparative Example 3
[0050] 2.32g of boron nitride nanosheets and 2.32g of Al2O3 were blended and added into a mixture of 8g of E51 epoxy resin, 5.84g of methylhexahydrophthalic anhydride curing agent and 0.12g of 2,4,6-tris(dimethylaminomethyl)phenol, and mixed evenly. After degassing, the mixture was molded and naturally cooled after curing to obtain an epoxy composite material.
[0051] The thermal conductivity of the sample was tested using the TC3000 thermal conductivity meter produced by Xi'an Xiaxi Technology Co., Ltd. The average value of the three measurements was taken as the final result. The test temperature was 30°C and the sample size was 30mm×40mm×3mm. The resistivity of the sample was measured using a broadband dielectric impedance spectrometer produced by German NOVOCONTROL. The sample was a disc with a diameter of 30mm and a thickness of 1mm.
[0052] The performance data of each sample are listed in Table 1.
[0053] Table 1 Comparison of performance of several composite materials
[0054]
[0055] It can be seen from the data in the table that the thermal conductivity of the MXene@BN epoxy composite material prepared in the present invention is much higher than that of other samples, and has excellent insulation performance.
[0056] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a MXene@BN heterostructure thermal conductive filler, characterized in that: The method comprises the following steps: 1) using a cationic modifier to modify the boron nitride nanosheets, adding the boron nitride nanosheets to an aqueous solution of the cationic modifier at a mass ratio of (1-10):1, at a modification temperature of 15-50° C., and for a modification time of 6-36 hours, to obtain modified boron nitride nanosheets with a positive charge on the surface; 2) Modifying the MXene nanosheets with an anionic modifier, adding the MXene nanosheets to an aqueous solution of the anionic modifier at a mass ratio of MXene nanosheets to anionic modifier of (1-10):1, at a modification temperature of 15-50°C, and for a modification time of 6-36h, to obtain modified MXene nanosheets with negatively charged surfaces; 3) electrostatically self-assemble the modified boron nitride nanosheets and the modified MXene nanosheets in a mass ratio of (10-100):1, at a temperature of 10-50° C., to obtain a MXene@BN heterostructure thermal conductive filler; Wherein, the MXene nanosheet is prepared as follows: Prepare a solution with concentrated hydrochloric acid and distilled water in a volume ratio of (2-4):1, stir and mix evenly, then add lithium fluoride, wherein the mass ratio of lithium fluoride to concentrated hydrochloric acid is 1:(10-20), slowly add Ti3AlC2 to the above solution, and stir at a temperature of 30-50°C for 1-2 days, wherein the mass ratio of Ti3AlC2 to lithium fluoride is 1:(1-2); after the reaction is completed, pour into a centrifuge tube and shake evenly, centrifuge for 5-8 minutes, pour out the supernatant, add 1M hydrochloric acid to the centrifuge tube, repeat the above centrifugation step 3-5 times, pour out the supernatant, add appropriate amount of distilled water to the centrifuge tube, repeat the above centrifugation step 5-7 times, pour out the upper layer, collect the bottom precipitate, add appropriate amount of distilled water, and ultrasonicate at room temperature for 40-70 minutes under nitrogen atmosphere, centrifuge the above mixed solution for 10-15 minutes, take the upper layer, and freeze-dry to obtain MXene nanosheets.
2. The method for preparing the heterogeneous structure thermal conductive filler according to claim 1, characterized in that: The cationic modifier is at least one selected from hexadecyltrimethylammonium chloride, polydimethyldiallylammonium chloride, and polydimethylsiloxane; the anionic modifier is at least one selected from polyvinyl alcohol sulfonate, sodium lauryl sulfate, and sodium polyacrylate.
3. An epoxy composite material of MXene@BN heterostructure thermal conductive filler prepared by the method of claim 1, characterized in that: The components and mass fractions of the epoxy composite material are as follows: The epoxy resin is one selected from bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic polyepoxy resin, alicyclic epoxy resin, and aliphatic epoxy resin; the curing agent is an amine curing agent or an acid anhydride curing agent; and the accelerator is one selected from phenol accelerators, tertiary amine accelerators, and substituted urea accelerators.
4. The epoxy composite material according to claim 3, characterized in that: The bisphenol A epoxy resin is epoxy resin E-51 or epoxy resin E-44, the bisphenol F epoxy resin is epoxy resin EP-862; the acid anhydride curing agent is selected from methyl hexahydrophthalic anhydride or maleic anhydride, the amine curing agent is 4,4'-diaminodiphenylmethane or 4,4'-diaminodiphenyl sulfone; the tertiary amine accelerator is 2,4,6-tris(dimethylaminomethyl)phenol or benzyldimethylamine.
5. The epoxy composite material according to claim 3 or 4, characterized in that: The components and mass fractions of the epoxy composite material are as follows:
6. A method for preparing the epoxy composite material as claimed in claim 3, characterized in that: The epoxy resin, curing agent and accelerator are uniformly mixed according to the ratio, and then the MXene@BN heterostructure thermal conductive filler is added, and the thermal conductive filler is evenly dispersed by stirring or ultrasonic vibration. After degassing and curing, the epoxy composite material is naturally cooled.
Citation Information
Patent Citations
Heterostructure heat-conducting filler, preparation method and application thereof, silicone rubber heat-conducting insulating composite material and preparation method of same
CN113087971A
MXene-silver heterostructure filler, polyvinyl alcohol heat-conducting electromagnetic shielding composite film and preparation method of polyvinyl alcohol heat-conducting electromagnetic shielding composite film
CN115850795A
Composite flexible film with electromagnetic shielding and heat conduction functions and preparation method thereof
CN112980056A
Flexible cellulose / boron nitride / MXene sandwich structure composite film as well as preparation method and application thereof
CN114456443A
Hollow microsphere composite heat-conducting filler coated with low-dimensional nano high-heat-conductivity material as well as preparation method and application of hollow microsphere composite heat-conducting filler
CN115612179A
Cited By
Preparation method of multifunctional composite coating on metal surface
CN120623821A
Flame retardant based on two-dimensional heterogeneous coupling structure, flame-retardant heat-conducting epoxy resin composite material and application of flame-retardant heat-conducting epoxy resin composite material
CN122445057A
MXene / multilayer boron nitride composite heat-conducting wave-absorbing material, preparation method and application thereof
CN122898251A